Clinical Classification of Mosaicism - Andrea Diociaiuti; Teresa Oranges; Eulalia Baselga; May El Hachem (JEADV Clinical Practice)
ABSTRACT The term ‘mosaic skin disorders’ encompasses conditions in which the skin is involved by mosaic mutations, including epidermal nevi, vascular nevi, connective tissue nevi and lipomatous nevi, among others. Mosaic skin abnormalities can present under a segmental pattern or as nonsegmental skin lesions. Nonsegmental mosaicism, which is most common, includes individual point lesions, tumours, hamartomatous lesions, or malformations, such as melanocytic nevi, Spitz tumours, and sporadic trichoepitheliomas. In some autosomal dominant genodermatoses with multiple skin lesions, a nonsegmental disseminated mosaicism emerges, often associated with neurological or multi‐organ involvement. A patchy skin involvement without midline separation is frequently observed in congenital melanocytic nevi. Segmental mosaicism is less common and presents as asymmetric cutaneous lesions in one or more separate body areas, respecting the body's midline. While the precise mechanisms remain uncertain, these segments possibly reflect clonal expansion of cells during prenatal development. In this article, we provide an overview of the types of mosaicism, discussing their patterns, clinical manifestations, and the varying degrees of severity associated with these conditions.